Análise dos aspectos legais e normativos de proteção da saúde e segurança dos trabalhadores com relação à radiação ionizante - Pereira, Ludmila Maria Perez de Barros (2009)
The subject studied in this dissertation deals with the legal structure related to protection of life and health of workers who provides services in areas where there is the occurrence of ionizing radiation, in order to describe and direct regulatory frameworks for the protection of occupational health for workers exposed to ionizing radiation, whether from industrial uses or Naturally Occurring Radioactive material, in the light of an Occupational Health and Safety Management System. Because of the risks and negative consequences that may arise for the employer in case of damage to workers' health due to worker exposure to ionizing radiation, a survey of the literature on aspects of administrative responsibility, labor, social security, civil and criminal related theme, in order to give an overview of the subject and demonstrate the importance of adopting appropriate protective measures. After making the waiver legislation, the main focus of the study rested on the standard CNEN NN-3.01, although she has not been edited through a law in formal direction, which is the main regulatory guidelines related to protection of health and safety of workers exposed to ionizing radiation and a critical analysis of some items of this standard has been made, aiming to contribute to its improvement, in order to give more legal security in its application, rank that, in the way as it is written currently, the referred to norm is subjects the questionings, if treating to the protection of the health of the worker displayed to the NORM proceeding from the activity of E&P